The politics of agricultural policy and nutrition: A case study of Malawi's Farm Input Subsidy Programme (FISP). - Helen Walls; Deborah Johnston; Mirriam Matita; Tayamika Kamwanja; Richard Smith; Simeon Nanama (Public Library of Science (PLoS), 2023)
The concept of food and nutrition policy has broadened from simply being an aspect of health policy, to policy interventions from across a wide range of sectors, but still with potentially important impact on nutritional outcomes. This wider and more complex conceptualisation involves policy with multiple objectives and stakeholder influences. Thus, it becomes particularly important to understand the dynamics of these policy processes, including policy design and implementation. To add to this literature, we apply the Kaleidoscope Model for understanding policy change in developing country contexts to the case-study of an agricultural input subsidy (AIS) programme in Malawi, the Farm Input Subsidy Programme (FISP), exploring the dynamics of the FISP policy process including nutritional impact. Over a three-month period between 2017 and 2019 we conducted in-depth interviews with key stakeholders at national and district levels, and focus groups with people from rural districts in Malawi. We also undertook a review of literature relating to the political economy of the FISP. We analysed the data thematically, as per the domains of the Kaleidoscope Model. The analysis across the FISP policy process including policy design and implementation highlights how stakeholders' ideas, interests and influence have shaped the evolution of FISP policy including constraints to policy improvement-and the nutritional impacts of this. This approach extends the literature on the tensions, contradictions and challenges in food and nutrition policy by examining the reasons that these occur in Malawi with the FISP. We also add to the political science and policy analysis literature on policy implementation, extending the concept of veto players to include those targeted by the policy. The findings are important for consideration by policymakers and other stakeholders seeking to address malnutrition in rural, food-insecure populations in Malawi and other low-income settings.